Q-Deformed Morse and Oscillator Potential - H. Hassanabadi; W. S. Chung; S. Zare; S. B. Bhardwaj (Advances in High Energy Physics)
We studied the q-deformed Morse and harmonic oscillator systems with appropriate canonical commutation algebra. The analytic solutions for eigenfunctions and energy eigenvalues are worked out using time-independent Schrödinger equation and it is also noted that these wave functions are sensitive to variation in the parameters involved.